Current perspectives and trends on the role of mitochondria in renal ischemia-reperfusion injury from 2005 to 2024: a bibliometric analysis and literature review - Yan, Rui; Zhang, Yalong; Li, Zewen; Li, Kunpeng; Man, Jiangwei; Yang, Li (Frontiers in Physiology, 2025)
BackgroundRenal ischemia-reperfusion injury (RIRI) represents a leading cause of acute kidney injury (AKI). Mitochondria, serving as the central organelles for cellular energy metabolism and signal transduction, play a pivotal role in the pathogenesis of RIRI.MethodsUtilizing the three major academic databases—Web of Science Core Collection (WoSCC), PubMed, and Scopus, this study conducted a comprehensive bibliometric analysis and visualization to explore research trends and key thematic areas related to mitochondrial involvement in renal ischemia-reperfusion injury from 2005 to 2024.ResultsBibliometric analysis reveals a sustained increase in research output concerning mitochondrial roles in RIRI over the past two decades. China and the United States have emerged as the most active contributors in this field. The U.S. Department of Veterans Affairs leads in terms of total publications, while Dong Zheng from the Second Xiangya Hospital of Central South University has contributed the highest number of publications by an individual author. Kidney International and the Journal of the American Society of Nephrology are the most frequently cited journals. This study systematically identified key research themes, including the mechanisms of mitochondrial dysfunction in RIRI, mitochondrial quality control mechanisms, and potential therapeutic strategies targeting mitochondria.ConclusionThrough bibliometric analysis, this study elucidates the knowledge structure and developmental trends in mitochondrial research related to RIRI. Over the past 20 years, mitochondrial dysfunction, mitochondrial quality control, and mitochondria-targeted therapeutic approaches have consistently constituted major research hotspots in this domain.